2016
DOI: 10.2320/matertrans.m2015272
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sub-Critical Heat Treatment on Hardness, Retained Austenite and Abrasive Wear Resistance of Hypoeutectic 16 mass% Cr-2 mass% Mo Cast Iron with Varying Vanadium Content

Abstract: To increase the matrix hardness without complete hardening, a sub-critical heat treatment was performed by holding the as-cast iron below the pearlite transformation temperature (A 1 ), and exposed to a hypoeutectic 16 mass% Cr-2 mass% Mo cast iron with a 03 mass% vanadium (V). The temperatures were held between 723 K and 923 K with 50 K intervals for 14.443.2 ks and then cooled via air from a fan. In the as-cast state, the hardness of the cast iron increased progressively and the volume fraction of retained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…These treatments (destabilization) have been reported in many research papers. However, the research on sub-critical heat treatment is quite limited [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These treatments (destabilization) have been reported in many research papers. However, the research on sub-critical heat treatment is quite limited [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the reference [10] the relationships between the subcritical heat treatment hardness, the volume fraction of retained austenite (V), and abrasive wear resistance of hypoeutectic 16% Cr-2% Mo cast irons with 0-3%V were investigated. It is found that the subcritical heat treatment can improve the hardness and wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]. High-chromium white cast irons are ferrous alloys containing 11-30% Cr and 1.8-3.6% C along with other alloying elements such as molybdenum and nickel [4,5]. The high chromium content in these cast irons provides them with excellent wear resistance, as chromium carbides are formed in the microstructure of the material.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of secondary carbides depends on a number of factors, including the chemical composition, the temperature and duration of the heat treatment, and the cooling rate after heat treatment. The morphology and characteristics of the carbides can also vary depending on these factors [5,[6][7][8][9][10][11][12]. These carbides can have different crystal structures, sizes, and distributions within the matrix, and can affect properties such as hardness, wear resistance, and toughness [11,13,14].…”
Section: Introductionmentioning
confidence: 99%